A catalyst for carbon dioxide hydrogenation reaction, a preparation method and application thereof
Patent Information
- Application Number
- CN202311369104.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-20
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2043-10-20
AI Technical Summary
[0008]本发明的目的是克服现有的二氧化碳加氢催化剂反应活性低、低碳烯烃选择性较低的缺点,提供一种用于二氧化碳加氢反应的催化剂、制备方法及其应用
[0052] (1) In this invention, boron nitride is used as the support, preferably a two-dimensional layered hexagonal boron nitride. This support exhibits excellent thermal conductivity (55 W/m K 25℃), superior thermal stability (air-resistant to 1000℃), and good corrosion resistance. Furthermore, after different treatments, it can possess a large specific surface area and excellent mechanical properties, making it a good substrate for constructing composite materials. This invention can prepare a catalyst for carbon dioxide hydrogenation in one step through a simple solvothermal reaction. This preparation method is simple to operate, has good reproducibility, uses green and inexpensive raw materials, and is suitable for large-scale production. No template agent is used in the preparation process, greatly reducing the introduction of heteroatoms into the catalyst.
Smart Images

Figure CN119857511B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of carbon dioxide utilization technology, specifically relating to a catalyst for carbon dioxide hydrogenation reaction, its preparation method, and its application. Background Technology
[0002] The gradual increase in global carbon dioxide emissions has triggered a series of severe environmental problems, such as the greenhouse effect. Therefore, the capture and comprehensive utilization of carbon dioxide (CO2) has received widespread attention. Among these, the hydrogenation of CO2 to produce high-value-added chemicals or liquid fuels is considered a promising research direction. This route can not only reduce the climate and environmental problems caused by CO2 but also produce high-value-added chemicals, reducing my country's current dependence on imported crude oil. Olefins, especially low-carbon olefins (C2-C4), are fundamental raw materials for the chemical industry and have significant application value, serving as an important indicator of a country's chemical industry level. my country's low-carbon olefins mainly come from traditional naphtha steam cracking, while my country relies heavily on imported oil. This high dependence on foreign oil, coupled with the non-renewable nature of petroleum, makes the production of low-carbon olefins through CO2 hydrogenation both an opportunity to increase the source of high-value-added chemicals such as olefins and a significant contribution to energy conservation and emission reduction.
[0003] Due to its molecular chemical inertness and high thermodynamic stability, the activation and selective conversion of carbon dioxide remains a highly challenging problem.
[0004] Existing patent CN106423263A discloses a catalyst for the hydrogenation of carbon dioxide to produce low-carbon olefins and its preparation method. This catalyst consists of a metal oxide and a molecular sieve. The metal oxide is composed of ZnO, ZrO2, and a support, and the molecular sieve is... Or a mixture of HY, this method has a low carbon dioxide conversion rate.
[0005] Patent CN108620089A discloses a catalyst for the hydrogenation of carbon dioxide to produce low-carbon olefins and its preparation method. The catalyst is an iron-based catalyst with manganese-modified surface. The method includes hydrothermal synthesis of magnetic Fe3O4 nanospheres and loading different amounts of manganese additives onto the surface of the obtained Fe3O4 nanospheres by impregnation. The catalyst has a uniform and controllable morphology and good reaction stability. However, the catalyst preparation process is complicated and requires the addition of surfactants, resulting in high catalyst preparation cost.
[0006] Patent CN 113797955 A discloses an iron-magnesium catalyst for the hydrogenation of carbon dioxide to produce low-carbon olefins. The method uses organic amines and ammonium bicarbonate as raw materials. It utilizes the buffering effect of ion pairs to control the microenvironment of the precipitation process, which can promote the uniform dispersion of iron and magnesium in the catalyst. The catalyst used in this method is mainly pure iron with a high iron content, so the conversion rate of iron per unit is low.
[0007] In recent years, Fe-based Fischer-Tropsch catalysts have attracted widespread attention in the preparation of low-carbon olefins due to their excellent reaction performance and industrial applications. However, the active metal Fe often has a strong interaction with the oxide support, which easily forms substances that are difficult to reduce, resulting in poor catalyst activity and selectivity. Conversely, a weak interaction between the metal and the support can easily lead to sintering and agglomeration of the active components. Summary of the Invention
[0008] The purpose of this invention is to overcome the shortcomings of existing carbon dioxide hydrogenation catalysts, such as low reactivity and low selectivity for low-carbon olefins, and to provide a catalyst, its preparation method, and its application for carbon dioxide hydrogenation. This invention uses boron nitride as a support, which has moderate interaction with the metal active components iron, manganese, and potassium. This catalyst exhibits high carbon dioxide hydrogenation reactivity and low-carbon olefin selectivity, particularly high CO2 conversion.
[0009] The first aspect of the present invention provides a catalyst for the hydrogenation reaction of carbon dioxide, comprising a boron nitride support and an active metal component supported on the boron nitride support, wherein the active metal component comprises iron, manganese and potassium.
[0010] According to some embodiments of the present invention, the active metal component is composed of iron, manganese and potassium.
[0011] According to some embodiments of the present invention, the catalyst is composed of a boron nitride support and an active metal component supported on the boron nitride support.
[0012] According to some embodiments of the present invention, in the catalyst, the active metal component iron accounts for 5% to 30% of the total mass of the catalyst, preferably 10% to 30%.
[0013] According to some embodiments of the present invention, the active metal component manganese accounts for 0.2% to 20% of the total mass of the catalyst, preferably 0.5% to 10%, and more preferably 0.5% to 8%.
[0014] According to some embodiments of the present invention, the active metal component potassium accounts for 0.1% to 5% of the total mass of the catalyst, preferably 0.25% to 3%, and more preferably 0.5% to 3%.
[0015] According to some embodiments of the present invention, the content of the active metal component in the catalyst is expressed as the mass of metal elements (iron, manganese, potassium).
[0016] According to some embodiments of the present invention, the specific surface area of the boron nitride is preferably 20 to 140 m². 2 / g, more preferably 70-140m 2 / g.
[0017] According to some embodiments of the present invention, the boron nitride is hexagonal boron nitride.
[0018] A second aspect of the present invention provides a method for preparing the above-mentioned catalyst, comprising:
[0019] A suspension containing iron, manganese, potassium and boron nitride is subjected to a solvothermal reaction.
[0020] According to some embodiments of the present invention, the temperature of the reaction is 100–200°C.
[0021] According to some embodiments of the present invention, the reaction time is 1 to 24 hours, preferably 6 to 24 hours.
[0022] According to some embodiments of the present invention, the solvothermal reaction is carried out in a hydrothermal synthesis reactor.
[0023] According to some embodiments of the present invention, the mixing method is stirring and / or ball milling; preferably, magnetic stirring or mechanical stirring is used.
[0024] According to some embodiments of the present invention, the preparation method further includes: after the reaction is completed, washing, centrifuging, drying, and calcining to obtain the catalyst; the drying temperature is preferably 60℃-120℃, and the drying time is preferably 5-24h; and / or, the calcination temperature is preferably 300℃~600℃, and the calcination time is preferably 3~12h.
[0025] According to some embodiments of the present invention, the catalyst uses an iron salt as the iron source, a manganese salt as the manganese source, and a potassium salt as the potassium source.
[0026] According to some embodiments of the present invention, the iron salt is selected from one or more of ferric chloride, ferric nitrate, ferrous acetate, ferric oxalate, and ferric acetylacetone (III) or their hydrates.
[0027] According to some embodiments of the present invention, the manganese salt is selected from one or more of manganese chloride, manganese nitrate, manganese acetate, manganese oxalate, and manganese acetylacetone (II) or their hydrates; the potassium salt is selected from one or more of potassium hydroxide, potassium carbonate, and potassium bicarbonate.
[0028] According to some embodiments of the present invention, the solvent used for the iron salt and / or manganese salt is selected from one or more of the following 1)-3): 1) water; 2) one or more of lower alcohols, N,N-dimethylformamide and toluene; 3) a mixture of water and lower alcohols; preferably, the lower alcohol is selected from one or more of methanol, ethanol, ethylene glycol and isopropanol, more preferably, the lower alcohol is ethylene glycol; and / or, the solvent used for the potassium salt is selected from one or more of water, methanol, ethanol, ethylene glycol, isopropanol, N,N-dimethylformamide and toluene.
[0029] According to some embodiments of the present invention, the preparation method further includes: preparing the suspension.
[0030] Preferably, the process of preparing the suspension specifically includes: mixing a mixed salt solution of iron and manganese salts with boron nitride, then adding a potassium salt solution and mixing to obtain the suspension; adding iron, manganese, and potassium salts stepwise to avoid the problem that direct mixing and addition of iron, manganese, and potassium salts would easily lead to a reaction and form ferric hydroxide precipitate, which is not conducive to the preparation of the catalyst.
[0031] More preferably, the process of preparing the suspension specifically includes:
[0032] The mixed salt solution of the iron and manganese salts was mixed with boron nitride and stirred for 2 to 4 hours;
[0033] After adding the potassium salt solution with stirring, continue stirring for 2 to 4 hours to prepare the suspension.
[0034] According to some embodiments of the present invention, the concentration of the mixed salt solution is 0.05 to 0.25 mol / L, and the molar ratio of Fe to Mn in the mixed salt is (3.75 to 20):1, preferably (8 to 10):1.
[0035] According to some embodiments of the present invention, the potassium salt solution has a concentration of 0.01 to 0.05 mol / L.
[0036] According to some embodiments of the present invention, the preparation method specifically includes:
[0037] (1) Prepare the mixed salt solution of the iron salt and manganese salt and the potassium salt solution;
[0038] (2) Mix the mixed salt solution of iron and manganese salts with boron nitride;
[0039] (3) Add potassium salt solution, mix, and obtain the suspension;
[0040] (4) The suspension undergoes a solvothermal reaction.
[0041] According to some embodiments of the present invention, the boron nitride is mixed with the iron source, manganese source and potassium source in the form of a boron nitride dispersion to obtain the suspension;
[0042] Preferably, the solvent of the boron nitride dispersion is selected from one or more of water, methanol, ethanol, ethylene glycol, isopropanol, benzene, toluene, N,N-dimethylformamide and N-methylpyrrolidone; preferably ethylene glycol, and the boron nitride dispersion is an ethylene glycol dispersion of boron nitride; the mass concentration of the ethylene glycol dispersion of boron nitride is preferably 1.0 to 3.0 g / L, more preferably 2.0 g / L.
[0043] The third aspect of the present invention provides the application of the above-described catalyst or the catalyst obtained by the above-described preparation method in the hydrogenation reaction of carbon dioxide;
[0044] According to some embodiments of the present invention, the carbon dioxide hydrogenation reaction is a reaction in which carbon dioxide is hydrogenated to produce low-carbon olefins.
[0045] According to some embodiments of the present invention, the temperature of the carbon dioxide hydrogenation reaction is 220°C to 450°C, the reaction pressure is 1.0 to 6.0 MPa, the reaction gas is a mixture of carbon dioxide and hydrogen, and the mass hourly space velocity of the reaction gas is 1000 to 20000 NL·kg. -1 ·h -1 The reactor is used for the hydrogenation of carbon dioxide, and the volume ratio of H2 to CO2 in the reactor is (1-5):1.
[0046] According to some embodiments of the present invention, the catalyst further includes a step of reducing the catalyst in a reducing atmosphere before catalyzing the hydrogenation reaction of carbon dioxide;
[0047] According to some embodiments of the present invention, the reducing atmosphere is hydrogen, the reducing pressure is 0.1 to 0.5 MPa, the reducing temperature is 280 to 400°C, and the reducing time is 2 to 24 h.
[0048] A fourth aspect of the present invention provides a method for producing low-carbon olefins by hydrogenation of carbon dioxide, the method comprising: contacting carbon dioxide and hydrogen with the catalyst described above or the catalyst obtained by the preparation method described above, wherein the catalyst catalyzes the hydrogenation reaction of carbon dioxide to produce low-carbon olefins.
[0049] Compared with existing technologies, this invention provides a catalyst for the hydrogenation reaction of carbon dioxide, its preparation method, and its application. This invention uses boron nitride as a support, which exhibits moderate interaction with the active metal components iron, manganese, and potassium.
[0050] Therefore, selecting a support with moderate metal-support interaction to improve the activity and stability of carbon dioxide hydrogenation and enhance the product selectivity of low-carbon olefins is of great significance. Boron nitride, as a graphite-like two-dimensional layered material, has advantages such as good thermal conductivity, excellent thermal stability, and good corrosion resistance. Furthermore, after different treatments, it can possess a large specific surface area and excellent mechanical properties, making it a good substrate for constructing composite materials.
[0051] The present invention has the following beneficial effects:
[0052] (1) In this invention, boron nitride is used as the support, preferably a two-dimensional layered hexagonal boron nitride. This support exhibits excellent thermal conductivity (55 W / m K 25℃), superior thermal stability (air-resistant to 1000℃), and good corrosion resistance. Furthermore, after different treatments, it can possess a large specific surface area and excellent mechanical properties, making it a good substrate for constructing composite materials. This invention can prepare a catalyst for carbon dioxide hydrogenation in one step through a simple solvothermal reaction. This preparation method is simple to operate, has good reproducibility, uses green and inexpensive raw materials, and is suitable for large-scale production. No template agent is used in the preparation process, greatly reducing the introduction of heteroatoms into the catalyst.
[0053] (2) The carbon dioxide hydrogenation catalyst prepared by the present invention makes full use of the advantages of boron nitride’s excellent thermal conductivity, good thermal stability and high reactivity of iron-based catalysts. The catalyst has the characteristics of easy reduction and carbonization, high CO2 conversion rate and high low carbon olefin selectivity, so it has broad application prospects in carbon dioxide hydrogenation reaction.
[0054] (3) The iron source required for the preparation of the catalyst in this invention is inexpensive and readily available.
[0055] (4) This invention can significantly improve the reaction performance of the catalyst by adjusting the ratio of metals in the raw materials, providing a new route for the efficient conversion of carbon dioxide to low-carbon olefins. Attached Figure Description
[0056] Figure 1 The image shows the XRD pattern of the catalyst prepared in Example 1 of this invention.
[0057] Figure 2 The image shows the H2-TPR spectrum of the catalyst prepared in Example 3 of this invention. Detailed Implementation
[0058] The present invention will be further described below with reference to specific embodiments. The scope of protection of the present invention is not limited to the following embodiments, but is determined by the claims.
[0059] It should be noted that the two or more aspects (or embodiments) disclosed in the context of this specification can be arbitrarily combined with each other, and the resulting technical solutions are part of the original disclosure of this specification and also fall within the protection scope of this invention.
[0060] The detection method described in this invention is a conventional technique in the field.
[0061] In the embodiments, the carbon dioxide hydrogenation reaction is carried out in one or more fixed-bed reactors, microchannel reactors, continuously stirred slurry-bed batch reactors, slurry bubble column reactors, or fluidized-bed reactors, and is carried out as a continuous or batch reaction process.
[0062] The method for preparing boron nitride and its dispersion is as described in the method disclosed in patent CN112536059A, but is not limited thereto.
[0063] The catalyst evaluation process used in this invention is as follows:
[0064] A certain amount of catalyst was placed in the isothermal section of a fixed-bed reactor. Before the carbon dioxide hydrogenation reaction, the catalyst was pretreated and activated for 12 hours at 400℃ in a hydrogen atmosphere. After the pretreatment, the reaction system was cooled to 280–360℃, and syngas (H2 / CO2 = (1–5):1) was introduced for reaction evaluation. Mass hourly space velocity (MHSV) was defined as the flow rate of H2 / CO2 syngas per unit mass of catalyst per unit time, and was controlled at 1000–20000 NL·kg during the reaction. -1 ·h -1 The gaseous products, including CO, CO2, H2, CH4, and C2-C9 hydrocarbons, were quantitatively analyzed by online gas chromatography. During the reaction, the tail gas flow rate was obtained using a wet scrubbing meter and used to calculate the CO2 conversion rate. Within one reaction cycle, the cold trap and hot trap were each drained once for component analysis and material balance calculation.
[0065] Example
[0066] The following describes exemplary embodiments of the present invention, including various details of the embodiments to aid understanding, and should be considered merely exemplary. Therefore, those skilled in the art will recognize that various changes and modifications can be made to the embodiments described herein without departing from the scope and spirit of the invention. Similarly, for clarity and brevity, descriptions of well-known functions and structures are omitted in the following description. Unless otherwise specified, the experimental methods used in the following embodiments are conventional methods. Unless otherwise specified, the materials, reagents, etc., used in the following embodiments are commercially available.
[0067] In the following exemplary embodiments of the present invention, the active metal component is defined by the elemental mass of the metal. Boron nitride is a two-dimensional layered hexagonal boron nitride, which has advantages such as good thermal conductivity (55W / m K 25℃), excellent thermal stability (air can withstand high temperature of 1000℃), and good corrosion resistance.
[0068] The following exemplary embodiment of the present invention describes a method for preparing a catalyst for the hydrogenation reaction of carbon dioxide, comprising the following steps:
[0069] Prepare mixed salt solutions of iron and manganese salts, potassium salt solutions, and ethylene glycol dispersions of boron nitride, respectively;
[0070] A mixed salt solution of iron and manganese salts was added to a boron nitride ethylene glycol (boron nitride / ethylene glycol) dispersion and stirred for 2–4 hours to obtain a stable and uniform suspension.
[0071] Add the potassium salt solution to the above suspension under stirring conditions, and continue stirring for 2 to 4 hours;
[0072] The resulting suspension was then transferred to a hydrothermal synthesis reactor and subjected to a solvothermal reaction at 100–200°C for 1–24 hours. The resulting product was washed, centrifuged, dried, and calcined to obtain the carbon dioxide hydrogenation catalyst.
[0073] Example 1
[0074] Preparation of the catalyst and testing of its carbon dioxide hydrogenation performance in this invention
[0075] (1) Dissolve ferric nitrate and manganese nitrate in water according to the Fe / Mn molar ratio of 30:8 (i.e. 3.75:1), and stir magnetically until completely dissolved to obtain a 0.25 mol / L nitrate solution. Prepare a 0.05 mol / L potassium carbonate aqueous solution.
[0076] (2) Add 22 mL of the mixed salt solution from step (1) dropwise to 500 mL of boron nitride / ethylene glycol dispersion (2 g / L) while mechanically stirring to obtain a stable and uniform suspension.
[0077] (3) Add the aqueous solution of potassium carbonate slowly to the suspension described in step (2) under mechanical stirring and continue stirring for 3 hours.
[0078] (4) Transfer the suspension from step (3) to a hydrothermal synthesis reactor and react at 180°C for 12 hours. After the reaction is complete, cool naturally to room temperature, wash with deionized water, centrifuge 3 to 5 times, and dry in an oven at 80°C for 12 hours to obtain a dry catalyst precursor.
[0079] (5) The dried catalyst precursor from step (4) is calcined in air at 500°C for 5 hours to obtain the catalyst. The catalyst composition is 30Fe8Mn3K / BN; wherein the contents of active metals iron, manganese, and potassium are 30%, 8%, and 3% of the total mass of the catalyst, respectively; except for the active metals, the rest of the catalyst is boron nitride; the surface area of boron nitride is 140 m². 2 / g. The XRD pattern of the catalyst is shown below. Figure 1 .
[0080] (6) Carbon dioxide hydrogenation performance test
[0081] The above catalyst (1 g) was placed in the isothermal section of a fixed-bed reactor. The catalyst was reduced in H2 at 400 °C and 0.3 MPa for 16 h. After cooling to 220 °C, the mixture was switched to syngas (H2 / CO2 = 3, volume ratio), pressurized to 3 MPa, and slowly heated to 350 °C at a syngas space velocity of 15000 NL·kg⁻¹. -1 ·h -1 The carbon dioxide hydrogenation reaction was carried out under the conditions shown in Table 1, and the CO2 conversion rate and low-carbon olefin selectivity of the reaction are shown in Table 1.
[0082] Example 2
[0083] Preparation of the catalyst and testing of its carbon dioxide hydrogenation performance in this invention
[0084] (1) Dissolve ferrous sulfate and manganese sulfate in dimethylformamide according to the Fe / Mn molar ratio of 20:1 and stir until completely dissolved to obtain a 0.05 mol / L mixed salt solution; and prepare an aqueous solution of 0.02 mol / L potassium hydroxide.
[0085] (2) Add 42.0 mL of the mixed salt solution from step (1) dropwise to 500 mL of boron nitride / ethylene glycol dispersion (2 g / L) while mechanically stirring to obtain a stable and uniform suspension.
[0086] (3) Add the aqueous solution of potassium hydroxide slowly to the suspension described in step (2) under mechanical stirring and continue stirring for 3 hours.
[0087] (4) Transfer the suspension from step (3) to a hydrothermal synthesis reactor and react at 140°C for 24 hours. After the reaction is complete, cool naturally to room temperature, wash with deionized water, centrifuge 5 to 8 times, and dry in an oven at 120°C for 8 hours to obtain a dry catalyst precursor.
[0088] (5) The dried catalyst precursor obtained in step (4) is calcined at 450°C for 8 hours in a helium atmosphere to obtain the catalyst. The catalyst composition is 10Fe0.5Mn0.25K / BN; wherein the contents of active metals iron, manganese, and potassium are 10%, 0.5%, and 0.25% of the total mass of the catalyst, respectively. Except for the active metals, the catalyst is composed of boron nitride, and the surface area of boron nitride is 100 m². 2 / g.
[0089] (6) Carbon dioxide hydrogenation performance test
[0090] The above catalyst (1 g) was placed in the isothermal section of a fixed-bed reactor. The catalyst was reduced in H2 at 350 °C and 0.2 MPa for 16 h. After cooling to 220 °C, the reactor was switched to syngas (H2 / CO2 = 2, volume ratio), pressurized to 3.0 MPa, and slowly heated to 340 °C at a syngas space velocity of 5000 NL·kg⁻¹. -1 ·h -1 The carbon dioxide hydrogenation reaction was carried out under the conditions shown in Table 1, and the CO2 conversion rate and low-carbon olefin selectivity of the reaction are shown in Table 1.
[0091] Example 3
[0092] Preparation of the catalyst and testing of its carbon dioxide hydrogenation performance in this invention
[0093] (1) Dissolve ferrous acetate and manganese acetate in water at a Fe / Mn molar ratio of 8:1, and stir until completely dissolved to obtain a 0.25 mol / L mixed salt solution. Prepare a 0.03 mol / L potassium bicarbonate ethanol solution.
[0094] (2) Add 21 mL of the mixed salt solution from step (1) dropwise to 500 mL of boron nitride / ethylene glycol dispersion (2 g / L) to obtain a stable and uniform suspension.
[0095] (3) Add the potassium bicarbonate ethanol solution slowly to the suspension in step (2) under mechanical stirring and continue stirring for 3 hours.
[0096] (4) Transfer the suspension from step (3) to a hydrothermal synthesis reactor and react at 160°C for 12 hours. After the reaction is complete, cool naturally to room temperature, centrifuge 3 to 5 times with deionized water, and dry in an oven at 120°C for 5 hours to obtain a dry catalyst precursor.
[0097] (5) The dried catalyst precursor obtained in step (4) is calcined in air at 400°C for 8 hours to obtain the catalyst. The catalyst composition is 20Fe2.5Mn0.8K / BN; wherein the contents of active metals iron, manganese, and potassium are 20%, 2.5%, and 0.8% of the total mass of the catalyst, respectively, and the surface area of boron nitride is 115m². 2 / g; the H2-TPR spectrum of the catalyst is shown in [reference needed]. Figure 2 The H2- temperature program controls the position of the reduction peak in two places.
[0098] (6) Carbon dioxide hydrogenation performance test
[0099] The above catalyst (1 g) was placed in the isothermal section of a fixed-bed reactor. The catalyst was reduced in H2 at 400 °C and 0.4 MPa for 24 h. After cooling to 220 °C, the reactor was switched to syngas (H2 / CO2 = 4, volume ratio), pressurized to 3.0 MPa, and slowly heated to 320 °C at a syngas space velocity of 10000 NL·kg⁻¹. -1 ·h -1 The carbon dioxide hydrogenation reaction was carried out under the conditions shown in Table 1, and the CO2 conversion rate and low-carbon olefin selectivity of the reaction are shown in Table 1.
[0100] Example 4
[0101] Preparation of the catalyst and performance testing of carbon dioxide hydrogenation according to this invention
[0102] (1) Dissolve ferric oxalate and manganese nitrate in water at a Fe / Mn molar ratio of 10:1 and stir until completely dissolved to obtain a 0.1 mol / L mixed salt solution. Prepare a 0.01 mol / L potassium carbonate ethylene glycol solution.
[0103] (2) Add 74 mL of the mixed salt solution obtained in step (1) dropwise to 500 mL of boron nitride / ethylene glycol dispersion (2 g / L) while mechanically stirring to obtain a stable and uniform suspension.
[0104] (3) Add the potassium carbonate ethylene glycol solution slowly to the suspension in step (2) under mechanical stirring and continue stirring for 4 hours.
[0105] (4) Transfer the suspension from step (3) to a hydrothermal synthesis reactor and react at 160°C for 8 hours. After the reaction is complete, cool naturally to room temperature, wash with deionized water, centrifuge 3 to 5 times, and dry at 60°C for 24 hours to obtain a dry catalyst precursor.
[0106] (5) The dried catalyst precursor from step (4) is calcined at 400°C for 12 hours under a nitrogen atmosphere to obtain the catalyst. The catalyst composition is 25Fe2.5Mn1.5K / BN, wherein the contents of active metals iron, manganese, and potassium are 25%, 2.5%, and 1.5% of the total mass of the catalyst, respectively, and the surface area of boron nitride is 140 m². 2 / g.
[0107] (6) Carbon dioxide hydrogenation performance test
[0108] The above catalyst (1 g) was placed in the isothermal section of a fixed-bed reactor. The catalyst was reduced in H2 at 340 °C and 0.1 MPa for 16 h. After cooling to 220 °C, the mixture was switched to syngas (H2 / CO2 = 2, volume ratio), pressurized to 4.0 MPa, and slowly heated to 340 °C at a space velocity of 20000 NL·kg⁻¹. -1 ·h -1 The carbon dioxide hydrogenation reaction was carried out under the conditions shown in Table 1, and the CO2 conversion rate and low-carbon olefin selectivity of the reaction are shown in Table 1.
[0109] Example 5
[0110] Preparation of the catalyst and performance testing of carbon dioxide hydrogenation according to the present invention
[0111] (1) Iron(III) acetylacetone and manganese acetylacetone were dissolved in toluene at a Fe / Mn molar ratio of 5:1 and stirred until completely dissolved to obtain a 0.15 mol / L mixed salt solution; and a 0.02 mol / L potassium carbonate ethylene glycol solution was prepared.
[0112] (2) Add 52 mL of the mixed salt solution obtained in step (1) dropwise to 500 mL of boron nitride / ethylene glycol dispersion (2 g / L) while magnetically stirring to obtain a stable and uniform suspension.
[0113] (3) Add the potassium carbonate ethylene glycol solution slowly to the suspension described in step (2) under magnetic stirring and continue stirring for 2 hours.
[0114] (4) Transfer the suspension from step (3) to a hydrothermal synthesis reactor and react at 140°C for 12 hours. After the reaction is complete, cool naturally to room temperature, wash with deionized water, centrifuge 3 to 5 times, and dry at 80°C for 16 hours to obtain a dry catalyst precursor.
[0115] (5) The dried catalyst precursor obtained in step (4) is calcined under nitrogen at 350°C for 12 hours to obtain the catalyst. The catalyst composition is 25Fe5Mn2K / BN; wherein the contents of active metals iron, manganese, and potassium are 25%, 5%, and 2% of the total mass of the catalyst, respectively, and the surface area of boron nitride is 130 m². 2 / g.
[0116] (6) Carbon dioxide hydrogenation performance test
[0117] The above catalyst (1 g) was placed in the isothermal section of a fixed-bed reactor. The catalyst was reduced for 24 h at 400 °C and 0.3 MPa under H2 atmosphere. After cooling to 220 °C, the mixture was switched to syngas (H2 / CO2 = 3, volume ratio), pressurized to 3.0 MPa, and slowly heated to 320 °C at a space velocity of 10000 NL·kg⁻¹. -1 ·h -1 The carbon dioxide hydrogenation reaction was carried out, and the CO2 conversion rate and low-carbon olefin selectivity of the reaction are shown in Table 1.
[0118] Comparative Example 1
[0119] Boron nitride-supported potassium manganese catalyst prepared by impregnation method and its performance in carbon dioxide hydrogenation.
[0120] (1) Dissolve ferric nitrate and manganese nitrate in water according to the Fe / Mn molar ratio of 30:8 and stir until completely dissolved to obtain a 0.25 mol / L mixed salt solution. Prepare a 0.05 mol / L potassium carbonate aqueous solution.
[0121] (2) A certain amount of the mixed iron-manganese salt solution obtained in step (1) is added dropwise to the hexagonal boron nitride while stirring continuously for 4 hours to obtain the intermediate product.
[0122] (3) The intermediate product obtained in step (2) is dried in an oven at 80°C for 12 hours to obtain the precursor of the catalyst.
[0123] (4) Take a certain amount of potassium carbonate aqueous solution, add it to the above catalyst precursor by impregnation with an equal volume, then let it stand for 6 hours, dry it at 80°C for 12 hours to obtain the dry catalyst precursor.
[0124] (5) The dried catalyst precursor in step (4) is calcined in air at 500°C for 5 hours to obtain the catalyst. The catalyst composition is 30Fe8Mn3K / BN, wherein the contents of active metals iron, manganese, and potassium are 30%, 8%, and 3% of the total mass of the catalyst, respectively; the specific surface area of the hexagonal boron nitride is 130 m². 2 / g.
[0125] (6) Carbon dioxide hydrogenation performance test
[0126] The above catalyst (1 g) was placed in the isothermal section of a fixed-bed reactor. The catalyst was reduced in H2 at 400 °C and 0.3 MPa for 16 h. After cooling to 220 °C, the mixture was switched to syngas (H2 / CO2 = 3, volume ratio), pressurized to 3 MPa, and slowly heated to 350 °C at a space velocity of 15000 NL·kg⁻¹. -1 ·h -1 The carbon dioxide hydrogenation reaction was carried out under the conditions shown in Table 1, and the CO2 conversion rate and low-carbon olefin selectivity of the reaction are shown in Table 1.
[0127] Comparative Example 2
[0128] Silica-supported iron-manganese-potassium catalyst prepared by impregnation method and its performance in carbon dioxide hydrogenation.
[0129] (1) Dissolve ferric nitrate and manganese nitrate in water according to the Fe / Mn molar ratio of 30:8 and stir until completely dissolved to obtain a 0.25 mol / L mixed salt solution. Prepare a 0.05 mol / L potassium carbonate aqueous solution.
[0130] (2) A certain amount of the mixed iron-manganese salt solution obtained in step (1) is added dropwise to silicon dioxide while stirring continuously for 4 hours to obtain an intermediate product.
[0131] (3) The intermediate product obtained in step (2) is dried in an oven at 80°C for 12 hours to obtain the precursor of the catalyst.
[0132] (4) Take a certain amount of potassium carbonate aqueous solution, add it to the above catalyst precursor by impregnation with an equal volume, then let it stand for 6 hours, dry it at 80°C for 12 hours to obtain the dry catalyst precursor.
[0133] (5) The dried catalyst precursor in step (4) is calcined in air at 500°C for 5 hours to obtain the catalyst. The catalyst composition is 30Fe8Mn3K / SiO2, wherein the contents of active metals iron, manganese, and potassium are 30%, 8%, and 3% of the total mass of the catalyst, respectively; the specific surface area of the silica is 140 m². 2 / g.
[0134] (6) Carbon dioxide hydrogenation performance test
[0135] The above catalyst (1 g) was placed in the isothermal section of a fixed-bed reactor. The catalyst was reduced in H2 at 400 °C and 0.3 MPa for 16 h. After cooling to 220 °C, the mixture was switched to syngas (H2 / CO2 = 3, volume ratio), pressurized to 3 MPa, and slowly heated to 350 °C at a space velocity of 15000 NL·kg⁻¹. -1 ·h -1The carbon dioxide hydrogenation reaction was carried out under the conditions shown in Table 1, and the CO2 conversion rate and low-carbon olefin selectivity of the reaction are shown in Table 1.
[0136] Comparative Example 3
[0137] Alumina-supported iron-manganese-potassium catalyst prepared by impregnation method and its performance in carbon dioxide hydrogenation.
[0138] (1) Dissolve ferric nitrate and manganese nitrate in water according to the Fe / Mn molar ratio of 30:8 and stir until completely dissolved to obtain a 0.25 mol / L mixed salt solution. Prepare a 0.05 mol / L potassium carbonate aqueous solution.
[0139] (2) A certain amount of the mixed iron-manganese salt solution obtained in step (1) is added dropwise to aluminum oxide while stirring continuously for 4 hours to obtain an intermediate product.
[0140] (3) The intermediate product obtained in step (2) is dried in an oven at 80°C for 12 hours to obtain the precursor of the catalyst.
[0141] (4) Take a certain amount of potassium carbonate aqueous solution, add it to the above catalyst precursor by impregnation with an equal volume, then let it stand for 6 hours, dry it at 80°C for 12 hours to obtain the dry catalyst precursor.
[0142] (5) The dried catalyst precursor in step (4) is calcined in air at 500°C for 5 hours to obtain the catalyst. The catalyst composition is 30Fe8Mn3K / Al2O3, wherein the contents of active metals iron, manganese, and potassium are 30%, 8%, and 3% of the total mass of the catalyst, respectively; the specific surface area of the alumina is 135 m². 2 / g.
[0143] (6) Carbon dioxide hydrogenation performance test
[0144] The above catalyst (1 g) was placed in the isothermal section of a fixed-bed reactor. The catalyst was reduced in H2 at 400 °C and 0.3 MPa for 16 h. After cooling to 220 °C, the mixture was switched to syngas (H2 / CO2 = 3, volume ratio), pressurized to 3 MPa, and slowly heated to 350 °C at a space velocity of 15000 NL·kg⁻¹. -1 ·h -1 The carbon dioxide hydrogenation reaction was carried out under the conditions shown in Table 1, and the CO2 conversion rate and low-carbon olefin selectivity of the reaction are shown in Table 1.
[0145] Comparative Example 4
[0146] Preparation and performance testing of FeMn / BN catalysts for carbon dioxide hydrogenation
[0147] (1) Dissolve ferrous acetate and manganese acetate in water according to the Fe / Mn molar ratio of 8:1, mix and stir until completely dissolved to obtain a 0.25 mol / L mixed salt solution.
[0148] (2) Add 21 mL of the mixed salt solution from step (1) dropwise to 500 mL of boron nitride / ethylene glycol dispersion (2 g / L) while mechanically stirring to obtain a stable and uniform suspension.
[0149] (3) Transfer the suspension from step (3) to a hydrothermal synthesis reactor and react at 160°C for 12 hours. After the reaction is complete, cool naturally to room temperature, centrifuge 3 to 5 times with deionized water, and dry in an oven at 120°C for 5 hours to obtain a dry catalyst precursor.
[0150] (4) The dried catalyst precursor obtained in step (4) is calcined in air at 400°C for 8 hours to obtain the catalyst. The catalyst composition is 20Fe2.5Mn / BN; wherein the contents of active metals iron, manganese, and potassium are 20% and 2.5% of the total mass of the catalyst, respectively, and the surface area of boron nitride is 115 m². 2 / g.
[0151] (5) Carbon dioxide hydrogenation performance test
[0152] The above catalyst (1 g) was placed in the isothermal section of a fixed-bed reactor. The catalyst was reduced in H2 at 400 °C and 0.4 MPa for 24 h. After cooling to 220 °C, the reactor was switched to syngas (H2 / CO2 = 4, volume ratio), pressurized to 3.0 MPa, and slowly heated to 320 °C at a syngas space velocity of 10000 NL·kg⁻¹. -1 ·h -1 The carbon dioxide hydrogenation reaction was carried out under the conditions shown in Table 1, and the CO2 conversion rate and low-carbon olefin selectivity of the reaction are shown in Table 1.
[0153] Comparative Example 5
[0154] Preparation and performance testing of FeK / BN catalyst for carbon dioxide hydrogenation
[0155] (1) Dissolve ferrous acetate in water and stir until completely dissolved to obtain a 0.25 mol / L mixed salt solution. Prepare a 0.03 mol / L potassium bicarbonate ethanol solution.
[0156] (2) Add 21 mL of the salt solution from step (1) dropwise to 500 mL of boron nitride / ethylene glycol dispersion (2 g / L) while mechanically stirring to obtain a stable and uniform suspension.
[0157] (3) Add the potassium bicarbonate ethanol solution slowly to the suspension in step (2) under mechanical stirring and continue stirring for 3 hours.
[0158] (4) Transfer the suspension from step (3) to a hydrothermal synthesis reactor and react at 160°C for 12 hours. After the reaction is complete, cool naturally to room temperature, centrifuge 3 to 5 times with deionized water, and dry in an oven at 120°C for 5 hours to obtain a dry catalyst precursor.
[0159] (5) The dried catalyst precursor obtained in step (4) is calcined in air at 400°C for 8 hours to obtain the catalyst. The catalyst composition is 20Fe0.8K / BN; wherein the contents of active metals iron, manganese, and potassium are 20% and 0.8% of the total mass of the catalyst, respectively, and the surface area of boron nitride is 115m². 2 / g.
[0160] (6) Carbon dioxide hydrogenation performance test
[0161] The above catalyst (1 g) was placed in the isothermal section of a fixed-bed reactor. The catalyst was reduced in H2 at 400 °C and 0.4 MPa for 24 h. After cooling to 220 °C, the reactor was switched to syngas (H2 / CO2 = 4, volume ratio), pressurized to 3.0 MPa, and slowly heated to 320 °C at a syngas space velocity of 10000 NL·kg⁻¹. -1 ·h -1 The carbon dioxide hydrogenation reaction was carried out under the conditions shown in Table 1, and the CO2 conversion rate and low-carbon olefin selectivity of the reaction are shown in Table 1.
[0162] Comparative Example 6
[0163] Preparation and performance testing of FeMnK / BN catalyst for carbon dioxide hydrogenation
[0164] (1) Iron(III) acetylacetone and manganese acetylacetone were dissolved in toluene at a Fe / Mn molar ratio of 5:1 and stirred until completely dissolved to obtain a 0.15 mol / L mixed salt solution; and a 0.02 mol / L potassium carbonate ethylene glycol solution was prepared.
[0165] (2) Add 52 mL of the mixed salt solution and the ethylene glycol solution of potassium carbonate obtained in step (1) dropwise to 500 mL of boron nitride / ethylene glycol dispersion (2 g / L), and stir magnetically at the same time to obtain a stable and uniform suspension, and continue stirring for 2 h.
[0166] (3) Transfer the suspension from step (2) to a hydrothermal synthesis reactor and react at 140°C for 12 hours. After the reaction is complete, cool naturally to room temperature, wash with deionized water, centrifuge 3 to 5 times, and dry at 80°C for 16 hours to obtain a dry catalyst precursor.
[0167] (4) The dried catalyst precursor obtained in step (3) is calcined under nitrogen at 350°C for 12 hours to obtain the catalyst. The catalyst composition is 25Fe5Mn2K / BN; wherein the contents of active metals iron, manganese, and potassium are 25%, 5%, and 2% of the total mass of the catalyst, respectively, and the surface area of boron nitride is 130 m². 2 / g.
[0168] (5) Carbon dioxide hydrogenation performance test
[0169] The above catalyst (1 g) was placed in the isothermal section of a fixed-bed reactor. The catalyst was reduced for 24 h at 400 °C and 0.3 MPa under H2 atmosphere. After cooling to 220 °C, the mixture was switched to syngas (H2 / CO2 = 3, volume ratio), pressurized to 3.0 MPa, and slowly heated to 320 °C at a space velocity of 10000 NL·kg⁻¹. -1 ·h -1 The carbon dioxide hydrogenation reaction was carried out, and the CO2 conversion rate and low-carbon olefin selectivity of the reaction are shown in Table 1.
[0170] Table 1. Activity and selectivity of the catalysts prepared in Examples 1-5 and Comparative Examples 1-6 for carbon dioxide hydrogenation.
[0171]
[0172] As can be seen from Table 1, the catalyst prepared in this invention has high CO2 conversion rate and high selectivity for low-carbon olefins.
[0173] It should be noted that the embodiments described above are only for explaining the present invention and do not constitute any limitation on the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory terms, not limiting terms. Modifications can be made to the present invention within the scope of the claims, and revisions can be made to the present invention without departing from the scope and spirit of the present invention. Although the present invention described herein relates to specific methods, materials, and embodiments, it does not mean that the present invention is limited to the specific examples disclosed herein; on the contrary, the present invention can be extended to all other methods and applications with the same function.
Claims
1. A method for preparing a catalyst for the hydrogenation reaction of carbon dioxide, characterized in that, The catalyst comprises a boron nitride support and an active metal component supported on the boron nitride support, wherein the active metal component comprises iron, manganese and potassium; The preparation method includes: subjecting a suspension containing an iron source, a manganese source, a potassium source and boron nitride to a solvothermal reaction; after the reaction is completed, washing, centrifuging, drying and calcining are performed to obtain the catalyst; The catalyst uses iron salt as the iron source, manganese salt as the manganese source, and potassium salt as the potassium source; the preparation method further includes: preparing the suspension, the specific process of preparing the suspension includes: mixing a mixed salt solution of iron salt and manganese salt with boron nitride, adding a potassium salt solution, mixing, and obtaining the suspension; The concentration of the mixed salt solution of iron and manganese salts is 0.05–0.25 mol / L, and the molar ratio of Fe to Mn in the mixed salt solution of iron and manganese salts is (3.75–20):1; the concentration of the potassium salt solution is 0.01–0.05 mol / L.
2. The preparation method according to claim 1, characterized in that, The active metal component is composed of iron, manganese, and potassium; and / or The catalyst consists of a boron nitride support and an active metal component supported on the boron nitride support.
3. The preparation method according to claim 1, characterized in that, In the catalyst, the active metal component iron accounts for 5% to 30% of the total mass of the catalyst; and / or, The active metal component, manganese, accounts for 0.2% to 20% of the total mass of the catalyst; and / or, The active metal component potassium accounts for 0.1% to 5% of the total mass of the catalyst; and / or, The specific surface area of the boron nitride is 20~140m². 2 / g; and / or, The boron nitride is hexagonal boron nitride.
4. The preparation method according to claim 3, characterized in that, In the catalyst, the active metal component iron accounts for 10% to 30% of the total mass of the catalyst; and / or, The active metal component, manganese, accounts for 0.5% to 10% of the total mass of the catalyst; and / or, The active metal component potassium accounts for 0.25% to 3% of the total mass of the catalyst; and / or, The specific surface area of the boron nitride is 70~140m². 2 / g.
5. The preparation method according to claim 4, characterized in that, In the catalyst, the active metal component manganese accounts for 0.5% to 8% of the total mass of the catalyst; and / or, The active metal component potassium accounts for 0.5% to 3% of the total mass of the catalyst.
6. The preparation method according to any one of claims 1-5, characterized in that, The reaction temperature is 100~200℃; and / or, The reaction time is 1-24 hours; and / or, The solvothermal reaction is carried out in a hydrothermal synthesis reactor; and / or, The mixing method is stirring and / or ball milling.
7. The preparation method according to claim 6, characterized in that, The reaction time is 6-24 hours; and / or, The mixing method is magnetic stirring or mechanical stirring.
8. The preparation method according to claim 1, characterized in that, The drying temperature is 60℃-120℃, and the drying time is 5-24h.
9. The preparation method according to claim 1, characterized in that, The calcination temperature is 300℃~600℃, and the calcination time is 3~12h.
10. The preparation method according to claim 1, characterized in that, The iron salt is selected from one or more of ferric chloride, ferric nitrate, ferrous acetate, ferric oxalate, and ferric acetylacetone (III) or their hydrates; and / or, The manganese salt is selected from one or more of manganese chloride, manganese nitrate, manganese acetate, manganese oxalate, and manganese acetylacetone (II) or their hydrates; and / or, The potassium salt is selected from one or more of potassium hydroxide, potassium carbonate, and potassium bicarbonate; and / or, The solvent used in the mixed salt solution of the iron and manganese salts is selected from any one or more of the following 1)-3): 1) water; 2) one or more of lower alcohols, N,N-dimethylformamide and toluene; 3) a mixture of water and lower alcohols; and / or, The solvent used in the potassium salt solution is selected from one or more of water, methanol, ethanol, ethylene glycol, isopropanol, N,N-dimethylformamide, and toluene.
11. The preparation method according to claim 10, characterized in that, The lower alcohol is selected from one or more of methanol, ethanol, ethylene glycol, and isopropanol.
12. The preparation method according to claim 11, characterized in that, The lower alcohol is ethylene glycol.
13. The preparation method according to any one of claims 1-5 and 7-12, characterized in that, The molar ratio of Fe to Mn in the mixed salt solution of the iron and manganese salts is (8~10):1; and / or, The process of preparing the suspension specifically includes: The mixed salt solution of iron and manganese salts is mixed with boron nitride and stirred for 2-4 hours; After adding the potassium salt solution with stirring, continue stirring for 2-4 hours to prepare the suspension.
14. The preparation method according to claim 13, characterized in that, The boron nitride is prepared by mixing the boron nitride dispersion with the mixed salt solution of the iron and manganese salts and the potassium salt solution to obtain the suspension.
15. The preparation method according to claim 14, characterized in that, The solvent for the boron nitride dispersion is selected from one or more of water, methanol, ethanol, ethylene glycol, isopropanol, benzene, toluene, N,N-dimethylformamide, and N-methylpyrrolidone.
16. The preparation method according to claim 15, characterized in that, The boron nitride dispersion is an ethylene glycol dispersion of boron nitride.
17. The preparation method according to claim 16, characterized in that, The mass concentration of the boron nitride glycol dispersion is 1.0~3.0 g / L.
18. The preparation method according to claim 16, characterized in that, The mass concentration of the boron nitride glycol dispersion is 2.0 g / L.
19. A catalyst obtained by the preparation method according to any one of claims 1-18.
20. The application of the catalyst according to claim 19 in the hydrogenation reaction of carbon dioxide.
21. The application according to claim 20, characterized in that, The carbon dioxide hydrogenation reaction is a reaction in which carbon dioxide is hydrogenated to produce low-carbon olefins; and / or, The carbon dioxide hydrogenation reaction is carried out at a temperature of 220℃ to 450℃ and a reaction pressure of 1.0 to 6.0 MPa. The reactant gas is a mixture of carbon dioxide and hydrogen, and the mass hourly space velocity (HSV) of the reactant gas is 1000 to 20000 NL·kg. -1 ·h -1 The reactor is used for the hydrogenation of carbon dioxide, and the volume ratio of H2 to CO2 in the reactor is (1~5):
1.
22. The application according to claim 20 or 21, characterized in that, The catalyst further includes a step of reducing the catalyst in a reducing atmosphere before catalyzing the hydrogenation reaction of carbon dioxide.
23. The application according to claim 22, characterized in that, The reducing atmosphere is hydrogen, the reducing pressure is 0.1~0.5MPa, the reducing temperature is 280~400℃, and the reducing time is 2~24h.
24. A method for producing low-carbon olefins by hydrogenation of carbon dioxide, the method comprising: Carbon dioxide and hydrogen are contacted with the catalyst of claim 19, which catalyzes the hydrogenation of carbon dioxide to produce low-carbon olefins.
Citation Information
Patent Citations
Catalyst for preparing low-carbon olefins by carbon dioxide hydrogenation and synthesis of low-carbon olefins
CN106423263A
Catalyst for preparing low-carbon olefin through carbon dioxide hydrogenation as well as preparation method and application of catalyst
CN108620089A
Iron oxide / boron nitride nano-catalyst as well as preparation method and application thereof
CN112536059A
Preparation and synthesis method and application of supported iron-based catalyst for preparing liquid fuel through carbon dioxide hydrogenation
CN113649010A